Between Struggle and Peaceful Dialogue: An Overture to Honneth and Ricoeur on Recognition - Bolaños, Paolo A. (Archīum Ateneo, 2024)
In this article I offer an overture to further discussions about the relationship between the German critical theorist, Axel Honneth, and the French philosopher of dialogue, Paul Ricoeur, specifically on their insights on the ethics of recognition. First, I define critical theory through the three normative resources suggested by Max Horkheimer in order to contextualize my reading of Honneth and Ricoeur, both of whom adhere to the politico-practical content of critical theory. Second, I briefly outline the Honneth–Ricoeur debate/dialogue in order to show the philosophical link between them. Third, in separate sections, I schematically discuss the basic features of their individual ethics of recognition in order to show the context of the idea of “struggle” and “peaceful dialogue.” Fourth, I present my critical comments on Ricoeur’s critique of Honneth. While I appreciate Ricoeur’s proposal for peaceful experiences of mutual recognition, I do think that his wariness of the Hegel–Honneth position on the normativity of struggle is not founded on convincing grounds.